To find the third term of the sequence, we substitute n = 3 into the rule:
A(3) = 12 + (3-1)(3)
A(3) = 12 + (2)(3)
A(3) = 12 + 6
A(3) = 18
So, the third term is 18.
To find the fourth term of the sequence, we substitute n = 4 into the rule:
A(4) = 12 + (4-1)(3)
A(4) = 12 + (3)(3)
A(4) = 12 + 9
A(4) = 21
So, the fourth term is 21.
To find the eleventh term of the sequence, we substitute n = 11 into the rule:
A(11) = 12 + (11-1)(3)
A(11) = 12 + (10)(3)
A(11) = 12 + 30
A(11) = 42
So, the eleventh term is 42.
Find the third, fourth, and eleventh terms of the sequence described by the rule.
A(n) = 12 + (n-1)(3)
Question content area bottom
Part 1
A()
enter your response here (Simplify your answer. Type an integer or a decimal.)
1 answer